2016
DOI: 10.5194/acp-16-15135-2016
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of retrieved noctilucent cloud particle properties from Odin tomography scans and model simulations

Abstract: Abstract. Mesospheric ice particles, known as noctilucent clouds or polar mesospheric clouds, have long been observed by rocket instruments, satellites and ground-based remote sensing, while models have been used to simulate ice particle growth and cloud properties. However, the fact that different measurement techniques are sensitive to different parts of the ice particle distribution makes it difficult to compare retrieved parameters such as ice particle radius or ice concentration from different experiments… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Moreover, the study by Megner et al (2016) suggested that the tomographic algorithm performs well for retrieving number density for small number densities (which usually occur lower in the cloud) but greatly underestimates it for high number densities (which usually occur higher up in the clouds, where the retrieval misses the smaller mode radius).…”
Section: Discussion Of Osiris Tomography Uncertaintiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the study by Megner et al (2016) suggested that the tomographic algorithm performs well for retrieving number density for small number densities (which usually occur lower in the cloud) but greatly underestimates it for high number densities (which usually occur higher up in the clouds, where the retrieval misses the smaller mode radius).…”
Section: Discussion Of Osiris Tomography Uncertaintiesmentioning
confidence: 99%
“…To overcome the limitation from the assumption of a spatially homogeneous cloud layer and to enable the retrieval of clouds as a function of actual height instead of tangent height, the application of a two-dimensional tomographic retrieval for OSIRIS has been presented by Hultgren et al (2013). The tomographic approach for OSIRIS retrievals (described in Section 2) provides a tool to study both vertical and horizontal variations of cloud microphysical properties on a local scale, which is useful for detailed studies of cloud growth and destruction (Christensen et al, 2016;Megner et al, 2016). An early attempt to apply a direct (tomographic) retrieval for a limb viewing instrument was investigated almost two decades ago.…”
mentioning
confidence: 99%
“…The Swedish-led Odin satellite (Murtagh et al, 2002) was launched on 20 February 2001, into an almost Sunsynchronous polar orbit at 600 km with ascending node near 18:00 local solar time. The Odin mission began as a joint project between aeronomy and astronomy, with the primary focus of the aeronomic part of the mission on coupling processes in the atmosphere, better understanding of ozone variation and processes in the middle atmosphere, and processes that govern PMC formation and mesospheric variability.…”
Section: Odin Osirismentioning
confidence: 99%
“…As a consequence, the PMC retrieval cannot separate low-lying clouds from clouds in the foreground or in the background. The PMC retrieval for the limb-viewing Optical Spectrograph and Infrared Imager System (OSIRIS) on the Odin satellite (Murtagh et al, 2002) assumes that the PMC layer is spatially homogeneous along the instrument line of sight (LOS) for the normal limb scans. This assumption is clearly a simplification, and numerous observations from nadir-viewing satellites, lidar and ground-based cameras (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The vertical structure of the NLC is strongly determined by the microphysics that governs cloud growth and sedimentation (Rapp and Thomas, 2006). The tomography will provide detailed insights in this vertical NLC evolution, including its possible modification by wave activity (Hultgren and Gumbel, 2014;Megner et al, 2016;Gao et al, 2018). However, since the vertical structure of the narrow NLC layers is dominated by microphysics rather than dynamical processes, a retrieval of vertical wavelengths of gravity waves will not be feasible from the NLC data.…”
Section: Measurement Conceptsmentioning
confidence: 99%